2018
DOI: 10.1007/s00431-018-3228-5
|View full text |Cite|
|
Sign up to set email alerts
|

Fecal calprotectin is not a clinically useful marker for the prediction of the early nonresponse to exclusive enteral nutrition in pediatric patients with Crohn disease

Abstract: Exclusive enteral nutrition (EEN) has been recommended as the first-line therapy in children with active Crohn disease (CD). The primary aim of our study was to determine whether it is possible to use the difference between basal fecal calprotectin (F-CPT) and the value at week 2 of EEN to predict clinical response at week 6. We prospectively collected stool samples for F-CPT analysis and clinical and laboratory parameters during EEN from 38 pediatric patients (28 boys, median age 12.8 years) with newly diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Similar results were obtained by Sipponen and Kolho [5]. In patients diagnosed with organic diseases, including IBD, calprotectin levels were reported to surpass 100 µg/g [19, 22]. On the basis of this test, high specificity was stated when normal levels were assumed as being <100 µg/g [22].…”
Section: Calprotectin and Ibdsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar results were obtained by Sipponen and Kolho [5]. In patients diagnosed with organic diseases, including IBD, calprotectin levels were reported to surpass 100 µg/g [19, 22]. On the basis of this test, high specificity was stated when normal levels were assumed as being <100 µg/g [22].…”
Section: Calprotectin and Ibdsupporting
confidence: 70%
“…The presence of high levels of FC was evidenced in the course of IBD [8, 20]. The first reports of this observation appeared in the 1990s; a positive correlation was observed between the calprotectin level and the intensity of inflammatory lesions in the intestines [10, 21, 22]. According to Pieczarkowski et al [23], a calprotectin level <100 µg/g concerns mainly patients with functional gastrointestinal disorder and children from the control group.…”
Section: Calprotectin and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, from adult studies, if no findings in endoscopy are reported, the frequency of detecting lesions when performing capsule endoscopy correlates with increasing FC values (FC < 50 mg/g, 10%; FC 50-100 mg/g, 25%; FC >100 mg/g, 62%) (116). With a rapid-onset therapeutic agent, such as Infliximab, the FC levels may drop back into the normal range within 2 weeks (89,117), although with exclusive enteral nutrition (EEN), the decline may be less clear and occur over a longer period of 6 to 8 weeks of therapy (79,(118)(119)(120)(121). The reduction of FC values during EEN; however, is lost rapidly after food re-introduction (118,122).…”
Section: Recommendationmentioning
confidence: 99%
“…However, there are conflicting reports on the prediction of the clinical response to changes in FC early after treatment. An early decrease in FC levels in children with luminal CD did not predict clinical response after six weeks of EEN induction therapy, and CR was predicted with low accuracy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%